2019
DOI: 10.1021/acs.jafc.9b00131
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between Bread Wheat and Spelt Grains Using Molecular Markers and Spectroscopy

Abstract: The increasing demand for spelt products requires the baking industry to develop accurate and efficient tools to differentiate between spelt and bread wheat grains. We subjected a 272-sample spelt-bread wheat set to several potential diagnostic methods. DNA markers for γ-gliadin-D (GAG56D), γ-gliadin-B (GAG56B), and the Q-gene were used, alongside phenotypic assessment of ease-of-threshing and near-infrared spectroscopy (NIRS). The GAG56B and GAG56D markers demonstrated low diagnostic power in comparison to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Enzyme-linked immunosorbent assay (ELISA) [9], chromatographic methods [9][10][11][12][13], near-infrared spectroscopy (NIRS) [14,15] and real-time PCR [16][17][18][19][20][21][22] and other molecular techniques [23] were used for the specific detection of cereal species in food. Compared to other analytical parameters, such as proteins and fats, DNA is sufficiently stable, depending on the degree of processing, to be detected even in more processed foods [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzyme-linked immunosorbent assay (ELISA) [9], chromatographic methods [9][10][11][12][13], near-infrared spectroscopy (NIRS) [14,15] and real-time PCR [16][17][18][19][20][21][22] and other molecular techniques [23] were used for the specific detection of cereal species in food. Compared to other analytical parameters, such as proteins and fats, DNA is sufficiently stable, depending on the degree of processing, to be detected even in more processed foods [24].…”
Section: Introductionmentioning
confidence: 99%
“…The barley system 1, based on the hordein gene and developed by zeltner et al, showed good specificity not only for Hordeum vulgare, but also for Hordeum murinum [21]. In addition, several systems claimed to be able to distinguish bread wheat from spelt [14,16,22].…”
Section: Introductionmentioning
confidence: 99%
“…Spelt Fatty acids profile [14] Triticum species PCR-RFLP (Q-locus) [15] Spelt RLP-LOC-CE, Real-time PCR (γ-gliadin) [16] Farro della Garfagnana in cereal mixtures padlock probe ligation and multiplex microarray [17] Spelt LC-MS peptide markers identification [18] Einkorn, emmer and spelt tubulin-based polymorphism (TBP) [19] Spelt PCR (γ-gliadin, Q-locus); NIR [20] Italian emmer landraces Spectroscopy and chemometrics [21] Spelt Duplex droplet digital PCR (Q-locus) [22] Most of the proposed assays are DNA-based methods used for the identification and quantification of spelt. Moreover, assays developed by Voorhuijzen et al [17] and by Foschi et al [21] are focused on the traceability of accessions specifically cultivated in Italian environments.…”
Section: Analytical Target Methods Referencementioning
confidence: 99%
“…γ-gliadin polymorphisms were exploited in the analytical protocols developed by Mayer et al [ 16 ] and by Curzon et al [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…22 Fingerprinting methods involving spectroscopy techniques have been developed that overcome the limits of targeted approaches and allow multiple wheat species authentication such as the DNA-based fingerprinting assay based on TBP 21 and an integrative near-infrared spectroscopic model based on Q gene classification for discrimination between spelt and bread wheat. 23 However, the practical application of these models may be hampered, especially in the case of multi-cereal mixtures, due to complexity of the models. In an overview of the most promising biomarkers and analytical tools for authentication of organic food products, Capuano et al 1 noted that a single marker was insufficient to confirm authenticity.…”
Section: Introductionmentioning
confidence: 99%